Prevalence of cryptococcal meningitis among people living with human immuno-deficiency virus and predictors of mortality in adults on induction therapy in Africa: A systematic review and meta-analysis - Muzazu, Seke G. Y.; Assefa, Dawit Getachew; Phiri, Christabel; Getinet, Tewodros; Solomon, Samrawit; Yismaw, Gizachew; Manyazewal, Tsegahun (Frontiers in Medicine, 2022)
Background: Cryptococcal meningitis (CM) is a leading cause of adult meningitis in countries with a high burden of HIV. It has remained a significant cause of morbidity and mortality in Africa despite the extensive rollout of HIV antiretroviral therapy (ART). This study aimed to systematically synthesize the evidence on the prevalence of CM among people living with HIV (PLWH) and its predictors of mortality among adults who are on induction antifungal therapy in Africa. Methods: PubMed/MEDLINE, Embase, and Google Scholar were searched for randomized clinical trials or observational studies published in Africa from 1995 to April 2021. Pooled prevalence of CM among PLWH was calculated using R-studio Version 1.4.1717 software and the data extracted from eligible studies were pooled as percentage with a 95% confidence interval (CI). Predictors of mortality among adults on induction antifungal therapy were synthesized narratively. Results: Out of 364 studies identified, 17 eligible articles were included in the analysis. The prevalence of CM among PLWH in Africa was 5.11% (95% CI 2.71-9.43%; participants = 10813; studies = 9; I2=97%). In the subgroup analysis, the prevalence was 12.9% (95% CI 4.883-30.0; participants = 533; studies = 3; I2= 63%) in the years 1995-2010 and 3.18% (95% CI 1.54-6.45; participants = 10280; studies = 6; I2= 98%) in the years 2011-2021, with the prevalence significantly decreased by 51% (p=0.02). Predictors of mortality were fluconazole monotherapy, focal neurological signs, low Glasgow coma scale, and delayed diagnosis of CM at varied timepoint. Conclusion: Prevalence of CM has significantly decreased from 1996-2010 to 2011-2021 among PLWH on induction therapy in Africa. fluconazole monotherapy, focal neurological symptoms, diastolic blood pressure <60mmHg, and concurrent tuberculosis coinfection were significant predictors of mortality at 2- and 10-weeks timepoints. CM remains a major concern among PLWH despite increases in ART coverage. Improved access to effective antifungal therapies is needed in Africa for timely initiation of combination induction therapy and better treatment outcomes of PLWH.